Determination of Integrated HPV58 Sequences in Cervical Lesions. Issue 7 (1st September 2012) - Li, Hui; Zhang, Ruifen; Cai, Yupin; Li, Yuan; Cheng, Xuemei; Zhu, Baoli; Yang, Yi; Xiang, Yang
Abstract : Integration of high-risk HPV in host genome is an important event in cervical cancer development. This study was aimed to analyze the integration of HPV58, a high-risk type that is prevalent in cervical lesions from southeastern Asia. Detection of integrated papillomavirus sequences by ligation-mediated polymerase chain reaction followed by DNA sequencing revealed 8 integrations in 5 samples, and virus integration was found present in 2 samples with early lesion. Sequence analysis of the viral-cellular junctions showed that E1 disruption in virus genome was an early and common event during HPV58 infection. In 6 integrations, DNA fragments of HPV58 genome integrated into the repetitive element sequences of host genome.